Utilization of farmer priority on local beef cattle development strategy in Central Java, Indonesia - Restiyana Agustine; Mujtahidah Anggriani Ummul Muzayyanah; Ahmad Romadhoni Surya Putra; Endang Baliarti (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Agustine R, Muzayyanah MAU, Putra ARS, Baliarti E. 2023. Utilization of farmer priority on local beef cattle development strategy in Central Java, Indonesia. Biodiversitas 24: 508-515. Indonesian local beef cattle, Peranakan Ongole (PO), is essential cattle breed predominantly raised by smallholder farmers in Central Java Province. Although it is generally perceived that raising PO cattle is not a regular source of income for the majority of farmers, however, there are few specific studies investigating the aspects and motives of farmers to keep their cattle. Therefore, this study is designed to explore the perspective of farmers leaders in Central Java, Indonesia, toward the priority aspects of raising PO cattle for their livelihoods. We selected Blora, Klaten, Grobogan, and Rembang as representatives of the study involving 29 farmers leaders with at least ten years of experience. Analytic Hierarchy Process was employed as a decision-making instrument to understand better various aspects used by PO cattle farmers. The results show that farmers consider investment function as their primary goal in raising PO cattle in all study areas. Then, farmers consider reproduction performance as the top priority aspect. In conclusion, the study revealed that smallholder farmers consider reproductive ability as a priority due to farmers make the investment function the main goal in raising PO cattle. Therefore, we recommended that farmers improve their knowledge regarding cows' reproduction through extension workers' assistance. Certainty on the PO cattle's selling price is needed so that raising PO cattle is feasible as an investment and stimulates the interest of farmers raising PO cattle.